Affordances are Signs - John Pickering (tripleC: Communication, Capitalism & Critique)
Peirce and Whitehead share a common project: to restrict the over-extension of reductionism, to show how matter must be sensate and to create an ontology of process and subjectivity. This article claims that biosemiotics can assist this project. Moreover, it shows that the concept of affordance is a means to produce a theory of causation that embraces physical, natural and cultural levels of order.